Using Local Ecological Knowledge in Louisiana to Infer Distribution and Abundance of the Alligator Snapping Turtle - Cybil C. Huntzinger; Irvin Louque Jr.; Eddie K. Lyons; Peter V. Lindeman; Will Selman (Wildlife Society Bulletin)
ABSTRACT Local ecological knowledge (LEK) collected via formal questionnaires and informal surveys can be a useful tool to aid in species conservation, particularly with species that are rare or difficult to detect. The alligator snapping turtle (Macrochelys temminckii) is a large aquatic turtle species that was heavily harvested by the commercial fishing industry beginning in the 1960s. This led to population declines throughout its range and closure of the commercial harvest in all states. The species is of conservation concern throughout its range and currently petitioned to be listed under the Endangered Species Act. However, the species' secretive behaviors and low densities can provide difficulties for biologists trying to determine accurate population densities and demographics. In 2013, we developed a LEK questionnaire to gauge licensed recreational fishermen on their perceptions of alligator snapping turtles, and distributed 2,100 questionnaires via postal service in a 7‐parish area of southwestern Louisiana, USA. Despite a low response rate (4.7%), all parishes had ≥1 sighting of alligator snapping turtle reported by respondents within the past 5 years, suggesting that they are still relatively widespread throughout southwestern Louisiana. However, respondents' perceptions also suggested that populations are stable to declining and tighter recreational harvest regulations may be needed to ensure long‐term population viability. Responses suggesting alligator snapping turtles' widespread distribution in southwestern Louisiana have recently been corroborated by field‐trapping surveys. This concordance suggests that LEK surveys can be useful for evaluating patterns of the distribution for cryptic species such as the alligator snapping turtle, while also potentially providing inferences about species abundance in a conservation context. Therefore, we recommend that surveys like this may assist with species monitoring when population sampling is logistically difficult or cost‐prohibitive. © 2019 The Wildlife Society.